The FIBRO DYSPLASIA OSSIFICANS PROGRESSIVA - Dogan, Emrah (Journal of Ayub Medical College Abbottabad, 2022)
Dear Editor; With great interest, I read the article titled Fibro Dysplasia Ossificans Progressiva (FOP) written by Waqas et al. (1), which was published in Jan-Mar 2019;31(1):123-126 of the J Ayub Med Coll Abbottabad. First of all, I would like to state that the article is very detailed and I have benefited from it in many points. It is the most detailed article I have reached while preparing my own article and its value as a case report is obvious. However, I would like to humbly highlight some parts of your paper. In the first sentence of this article, it is mentioned that FOP is the same disease as myositis ossificans. There are roughly four types of myositis ossificans as myositis ossificans circumscripta, myositis ossificans progressiva, panniculitis ossificans, fibro-osseous pseudotumor of the digits. The synonym of FOP is correctly myositis ossificans progressiva. Additionally, named as Stoneman's disease. When myositis ossificans is mentioned in the literature, it means generally heterotopic ossifications that occur mostly after trauma thus it is the first type which is myositis ossificans circumscripta. Also, it is said in the article that the disease was described by Guy Patin in 1968. This is a very distant period from the era of Patin's life. John Freke published the first scientific paper in 1740 about FOP. However, FOP was the first time described by Guy Patin before Freke (2). The letter sent by Patin to his colleague is accepted as the only proof that he found the disease (3). In some esteemed journals, different dates such as 1648 (4), 1692 (5),1693 (6) were mentioned. Let's mention that Patin died in 1672 (7). Probably 1648 was the correct date of description of the disease. Patin described the disease in his letter as follows '˜' I saw a woman today who finally became hard as wood all over" (8). Probably, it is for the reason why it is also named Stoneman's disease (9). I congratulate the authors for a magnificent, detailed and very well-structured report with perfect inspection, physical examination and radiological shares, especially for this rare case report.